1997
DOI: 10.4315/0362-028x-60.10.1167
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of Escherichia coli O157:H7 Strains Expressing Firefly Luciferase and Green Fluorescent Protein and Their Use in Survival Studies

Abstract: The firefly (Photinus pyralis) luciferase (luc) gene on plasmid vector pBESTluc and the Aequorea victoria green fluorescent protein (gfp) gene on plasmid vector pGFP were introduced into strains of Escherichia coli O157:H7. The recombinant E. coli strains were indistinguishable from their parent strains in biochemical and immunological assays and in a multiplex PCR reaction. There was no significant difference in the growth kinetics of the luc-bearing recombinants and the parent strains. At 37°C all of the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
85
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 4 publications
1
85
1
Order By: Relevance
“…This strain does not produce the Shiga-like toxins I and II (Stx1 Ϫ Stx2 Ϫ ) and contains the pGFP cDNA vector (Clontech Laboratories, Inc., Palo Alto, CA) expressing GFP and ampicillin resistance. The survival characteristics of this strain were indistinguishable from those of the wild-type strain (20). Kudva et al (33) reported no differences in survival in bovine manure and manure slurry between toxin-positive (Stx1 ϩ Stx2 ϩ ) and toxin-negative (Stx1 Ϫ Stx2 Ϫ ) E. coli O157:H7 strains.…”
Section: Methodsmentioning
confidence: 85%
“…This strain does not produce the Shiga-like toxins I and II (Stx1 Ϫ Stx2 Ϫ ) and contains the pGFP cDNA vector (Clontech Laboratories, Inc., Palo Alto, CA) expressing GFP and ampicillin resistance. The survival characteristics of this strain were indistinguishable from those of the wild-type strain (20). Kudva et al (33) reported no differences in survival in bovine manure and manure slurry between toxin-positive (Stx1 ϩ Stx2 ϩ ) and toxin-negative (Stx1 Ϫ Stx2 Ϫ ) E. coli O157:H7 strains.…”
Section: Methodsmentioning
confidence: 85%
“…All cores were inoculated with a rifamycin-resistant derivative of E. coli O157:H7 strain B6914 containing plasmid pGFP with genes for green fluorescent protein and ampicillin resistance (8). B6914 was grown to the mid-log phase in Luria-Bertani broth (Gibco BRL, Gaithersburg, Md.)…”
Section: Methodsmentioning
confidence: 99%
“…This strain does not produce Shiga-like toxins I and II (Stx1 Ϫ Stx2 Ϫ ) but contains the pGFP cDNA vector (Clontech Laboratories, Inc., Palo Alto, CA) expressing green fluorescent protein (GFP) and ampicillin resistance. The survival characteristics of the GFP-labeled strain were indistinguishable from those of the wild-type strain (13). In addition, Kudva et al (26) reported no differences in survival in bovine manure and manure slurry between toxin-positive (Stx1 ϩ Stx2 ϩ ) and toxin-negative (Stx1 Ϫ Stx2 Ϫ ) E. coli O157:H7.…”
Section: Methodsmentioning
confidence: 95%
“…Escherichia coli O157:H7 strain B6-914 gfp-91 was kindly provided by Pina Fratamico (13). This strain does not produce Shiga-like toxins I and II (Stx1 Ϫ Stx2 Ϫ ) but contains the pGFP cDNA vector (Clontech Laboratories, Inc., Palo Alto, CA) expressing green fluorescent protein (GFP) and ampicillin resistance.…”
Section: Methodsmentioning
confidence: 99%